Pelatihan “Fun with English” Untuk Siswa SMP Sebagai Upaya Peningkatan Kemampuan Bahasa Inggris - Pratika Ayuningtyas (LPPM Universitas Flores, 2021)
English is a global language which students should master to be able to be part of global world. Many hinders in learning English made the government and the education institution should work together in solving this problem. A short course namely Fun with English then proposed to omit the problem. The purpose of this course was to improve students’ communication skills in using English as well as improving their motivation and confidence. The program was done for two months. The participant of this program was the students from the nearby junior high school. After finishing the program students felt motivated less anxious and more confident in using English as their everyday language. It is expected that the similar program could be done regularly.